IMPLEMENTASI METODE EVERYONE IS TEACHER HERE PADA PEMBELAJARAN TEMATIK TERINTEGRASI KELAS IV SEMESTER II SUBTEMA SIKAP KEPAHLAWANAN SD PETOMPON 01 SEMARANG - Rahmawati, Intan; Fahmi, Syta Nuril (Universitas PGRI Semarang, 2014)
The use of various methods lead to the level of student understanding of the material becomes less. Characteristics of students who are active are less channeled into things - a positive thing because the use of methods that are less varied. The purpose of this study was to describe the implementation method Teacher Everyone Is Here on integrated thematic teaching fourth grade II subtema semsester Heroism attitude SD Petompon 01 Semarang.This study used a qualitative research approach that research procedures that produce descriptive data in the form of words written or spoken of people and behaviors that can be observed. Processing the data using descriptive analysis by stating the percentage of research results in the form of observations in the form of a percentage is used to describe the percentage of the observation of teacher learning and student attitudes during the learning process.The results showed that the average of the results of observations of learning that has been done by the teacher showed a